Key Factors Influencing Functionality of Community-Managed Rural Water Supply System in Nepal - Yadav, Maheshwar Prasad (Nepal Journal of Multidisciplinary Research, 2023)
The paper aims at examining key factors influencing the functionality of the community-managed rural water supply system in developing countries like Nepal. The study adopts a descriptive cum analytical research design based on primary data only. The required data were collected through a telephone interview using a semi-structured questionnaire on a sample of 486 respondents from the respective community-managed rural water supply projects. The collected data were analyzed using correlation, chi-square test, Cramer’s V, and cross-tabulation to find out the results leading to major findings of the study. The study concludes that the key factors influencing the functionality of the community-managed rural water supply system are the systems’ caretakers followed by the operation and maintenance fund, the activeness of the users’ committee, and the availability of spare parts in the context of Nepal.